The influence of polygamy on the academic achievements of pupils in Bubi District - Ndlovu, Bongiwe (Midlands State University, 2017)
This research sought to find out the extent to which polygamy influences the pupils in their academic achievement in Bubi District. The researcher employed the descriptive survey design method. Data was collected through the use of questionnaires for pupils and for teachers and an interview schedule for School Heads and senior teachers. The population was made up of five secondary schools in Bubi district. The sample comprised of thirty pupils, (six pupils from each school), twenty five teachers, (five teachers from each school) as well as the school heads and senior teachers. Snowballing and random sampling were used as the sampling techniques. The study established that polygamy does influence pupils’ academic achievement to some extent. The elements of what could negatively or positively influence the academic achievements of pupils but it was found out that negative influences of polygamy were more than positive influences. Family relationships, financial position of the family, availability and non-availability of school resources, academic level of parents and family size are among the factorsthat influenced the academic achievement of pupils from polygamous families.The study recommends that teachers should have a good knowledge of pupils’ background so as to address pupils according to their needs. In addition to that, school heads should make school policies and put binding measures to parents who do not attend consultation days. Pupils constantly need to be counseled so as not to lose focus due to family issues and therefore placement of qualified counselors in schools is recommended. In areas where cash flow is seasonal, heads of schools and SDC, should capitalize on the season when the cash flow will be high and make parents pay the yearly fees and buy all the school requirements for the year.Parents and the school heads should work together so as to help the children achieve their academic goals.